Association between air pollution and cerebrospinal fluid alpha-synuclein in urban elders: the CABLE study - Wang, An-Yi; Hu, He-Ying; Sun, Yan; Ou, Ya-Nan; Ma, Ya-Hui; Li, Meng; Li, Qiong-Yao; Tan, Lan (Frontiers in Aging Neuroscience, 2024)
Introduction Increasing evidence suggests that air pollution has a significant impact on the development of synucleinopathies, but the potential neurobiological mechanisms are unknown. We aimed to explore the associations of air pollution (including ozone [O3], nitrogen dioxide [NO2], and particulate matter [PM2.5]) with CSF α-syn levels in urban older adults. Methods We included 933 urban participants from the Chinese Alzheimer’s Biomarker and LifestylE study. The 5-year average levels of air pollution exposure were estimated in the areas of residence. Multivariate linear regression was conducted to detect the correlation of air pollution with CSF α-syn levels. Subgroup analyses by age, gender, season, and history of coronary heart disease (CHD) were performed. Moreover, restricted cubic spline (RCS) models were applied to explore the potential nonlinear relationships. Results We found a significant correlation of CSF α-syn level with PM2.5 in urban participants. Specifically, multiple linear regression showed a significant negative association between PM2.5 and CSF α-syn level (p = 0.029), which was more significant in female, midlife, non-CHD, and cold season subgroups. Besides, RCS models showed that O3 had an inverse J-shaped association with CSF α-syn levels in urban participants (p for nonlinearity = 0.040), and the harmful effect possibly appeared when O3 was above 37.9 ppb. Discussion Long-term exposure to air pollution was associated with lower CSF α-syn levels, which may offer a new direction for exploring and preventing synucleinopathies.